THE DEVELOPMENT OF MICROECONOMIC THEORY LEARNING MODULES - Syafaatul Hidayati (UIR PRESS, 2023)
The purpose of this study is to develop a learning module for microeconomic theory courses. This research uses the stages of 4-D model development which is carried out through 4 stages, namely defining, planning, development, and deployment. The stage of defining researchers conducts early-end analysis, student analysis, material analysis, task analysis, learning outcomes analysis. The next stage is planning. At this stage, the preparation of the Semester Learning Plan (RPS) is carried out as a reference in writing material and designing learning modules for microeconomic theory. In addition, at this stage, an initial draft of the development product is also prepared. The next stage is development. At the stage of the development process, it aims to create a product for the development of microeconomic theory learning modules that have been revised by expert validators. The validation of the microeconomic theory module was carried out by two experts, including material experts and media experts twice. The learning modules developed were declared feasible after going through two expert tests, both material experts and media experts. Material experts state the final assessment percentage at 90% and media experts at 93%. The final stage is deployment. The learning module of the microeconomic theory course learning module development product has an ISBN, with an ISBN number: 978-602-50986-4-2 and IPR with the application number and date EC00202001295, so that with this the product development of the microeconomic theory learning module is ready to be disseminated.